Continuous-flow system for horseradish peroxidase enzyme assay comprising a packed-column, an amperometric detector and a rotating bioreactor - Salinas, Eloy (2005)
The roles of chemical kinetics and mass transfer in three types of bioreactors (packed-column reactors, rotating disk bioreactors and amperometric detector), used with continuous-flow sample/reagent(s) processing, are discussed in detail. A normalized quantitative comparison between these types of reactors clearly shows that rotating disk reactors afford a significantly more efficient utilization of active sites and permit the effective utilization of very small amounts of biocatalysts. Horseradish peroxidase (EC 1.11.1.7), in presence of hydrogen peroxide catalyses the oxidation of [Os(bpy)2Cl(pyCOOH)]Cl. The electrochemical reduction back of this cosubstrate is detected on glassy carbon electrode surface at 0.00 V. Furthermore, the critical effect of substrate and cosubstrate concentration on amperometric immunosensors construction in which HRP is used as an enzymatic label was studied.